THE RACISM AND RESISTANCE STRATEGIES IN AMMA ASANTE’S MOVIE WHERE HANDS TOUCH (2018) - Zeni Zanuba Fazriyah (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
This study discusses the representation of racism and the types of resistance strategies to counter racist acts in the movie Where Hands Touch by Amma Asante. The focus of this research is on the main character, Leyna who is of mixed black and white descent. Black people who were not accepted in society in the Nazi era are a major problem to research. In the film Leyna gets racist acts because she has black ancestry. This study uses the Critical Race Theory by Richard Delgado and Jean Stefancic (2001) and Resistance Strategies concept by Shorter-Gooden (2004) to be related to the data in the movie. The results of the study show that Leyna experiences 6 types of racism-- Everyday Racism; Material Determinism; Social Construction; Differential Racialization; Intersectionality; and Voice Color --based on the Critical Race Theory by Ricard Delgado and Jean Stefancic and uses 3 types of resistance strategies - Internal Source, External Source, and Specific Resistance - for resist racism. Keywords: Black people, Racism, Resistance Strategies.